2020
DOI: 10.3390/molecules25143251
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Evaluation of New Coumarin Derivatives as Antioxidant, Antimicrobial, and Anti-Inflammatory Agents

Abstract: New pyranocoumarin and coumarin-sulfonamide derivatives were prepared and evaluated for their antioxidant, antimicrobial, and/or anti-inflammatory activities. Coumarin-sulfonamide compounds 8a–d demonstrated significant antioxidant activity, while 7c,d, 8c,d, and 9c,d exhibited antimicrobial activity equal to or higher than the standard antimicrobials against at least one tested microorganism. Regarding the anti-inflammatory testing, pyranocoumarins 2b, 3a,b and 5c and coumarin-sulfonamide compound 9a showed m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
53
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(55 citation statements)
references
References 35 publications
(38 reference statements)
2
53
0
Order By: Relevance
“…The classical CA inhibitors (CAIs) are the primary sulfonamides, which coordinate the zinc ion with their terminal deprotonated nitrogen atom and have been in clinical use for more than 70 years as diuretics and systemically acting antiglaucoma drugs [ 10 ]. Chromenes have attracted the interest of the scientific community due to their wide range of biological activities, such as antimicrobial [ 11 , 12 ], anticancer [ 13 , 14 ], anti-inflammatory [ 15 , 16 ], and CA inhibitors [ 17 , 18 , 19 , 20 , 21 ], nematicidal [ 22 ], antiallergic [ 23 ] Some sulfonamides also show antimicrobial [ 24 , 25 ], anticancer [ 26 , 27 ], antidiabetic [ 28 ], anti-inflammatory [ 15 , 29 ], and antitubercular [ 30 ] activities. Taking into account all of the above-mentioned, here we report the synthesis of (4-sulfamoylphenyl)-4 H -chromene-2-carboxamide derivatives for its incorporation into one scaffold chromene and sulfonamide moieties.…”
Section: Introductionmentioning
confidence: 99%
“…The classical CA inhibitors (CAIs) are the primary sulfonamides, which coordinate the zinc ion with their terminal deprotonated nitrogen atom and have been in clinical use for more than 70 years as diuretics and systemically acting antiglaucoma drugs [ 10 ]. Chromenes have attracted the interest of the scientific community due to their wide range of biological activities, such as antimicrobial [ 11 , 12 ], anticancer [ 13 , 14 ], anti-inflammatory [ 15 , 16 ], and CA inhibitors [ 17 , 18 , 19 , 20 , 21 ], nematicidal [ 22 ], antiallergic [ 23 ] Some sulfonamides also show antimicrobial [ 24 , 25 ], anticancer [ 26 , 27 ], antidiabetic [ 28 ], anti-inflammatory [ 15 , 29 ], and antitubercular [ 30 ] activities. Taking into account all of the above-mentioned, here we report the synthesis of (4-sulfamoylphenyl)-4 H -chromene-2-carboxamide derivatives for its incorporation into one scaffold chromene and sulfonamide moieties.…”
Section: Introductionmentioning
confidence: 99%
“…A study by Vakili et al (2012) reported that saffron or its active ingredients could significantly decrease oxidative damage in ischemic tissues such as the brain [37]. Coumarin-dependent compounds have antimicrobial and anti-inflammatory activities [38], and such compounds have different biological properties, including antioxidant activity in laboratory conditions [16], and inhibition of cell proliferation [39].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, extensive work has previously focused on the development of efficient and novel antioxidants and anti-inflammatory molecules. Various natural antioxidants have been characterized, and several anti-inflammatory agents, such as aspirin, are widely used [32]. However, the development of effective anti-inflammatory agents is still necessary.…”
Section: Discussionmentioning
confidence: 99%